Prevalence of conventional cardiovascular risk factors in patients with acute coronary syndromes in Slovakia - Alberty, Roman; Studenčan, Martin; Kovář, František (Central European Journal of Public Health, 2017)
BACKGROUND: Acute coronary syndrome (ACS) is a major health problem and the leading cause of death and disability in Slovakia. This is the first study to describe the prevalence rate of conventional cardiovascular risk factors in patients hospitalized for ACS. METHODS: Hypertension, diabetes mellitus, hyperlipidemia and cigarette smoking were documented in 1,567 cases (mean age, SD: 66.1±12.0 years, 34.8% of females) enrolled in the SLOVAKS registry from August 2011 through September 2011. RESULTS: Overall, 83.5% (95% CI, 81.6-85.2%) of the patients with ACS had hypertension, 65.0% (62.5-67.2%) had a hyperlipidemic profile, 32.6% (30.3-34.9%) were diagnosed with diabetes, and 27.6% (25.1-29.8%) were smokers at the time of a heart-related event. Only 5% of patients with ACS lacked any of the 4 conventional risk factors. Higher prevalence rates of all major risk factors, except smoking, were detected in women than in men, in older (≥65 years of age) than younger patients, and in rural (<2,000 inhabitants) than in urban areas. Premature ACS (<45 years of age) was associated with smoking in men, and smoking and hypertension in women. Smoking, in all risk factor combinations, reduced the age at the time of a heart-related event, on average, by 10.0 years in men and by 12.4 years in women. CONCLUSIONS: The results of this study suggest an appreciable burden of major cardiovascular risk factors and also highlight differences that may aid the targeting of public health interventions.
Keywords: dospělí; Acute Coronary Syndrome; zdravotnické přehledy; Female; Prevalence; Age Factors; Adult; ženské pohlaví; Registries; Slovakia; věkové faktory; lidé; Risk Factors; prevalence; retrospektivní studie; Male; Aged; rizikové faktory; lidé středního věku; registrace; Slovenská republika; senioři; akutní koronární syndrom; mužské pohlaví; Health Surveys; Retrospective Studies; Middle Aged; Humans